أثر تطوير معايير التدقيق العراقية في الإيفاء بمتطلبات الإصلاح ومناهضة الفساد: دراسة مقارنة تحليلية مع وضع إطار مقترح لتعديل دليل التدقيق العراقي رقم(6) بشأن تخطيط عملية التدقيق والإشراف عليه (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research aimed to statement, which impact that the development of Iraqi auditing standards in the fight against corruption and to fulfill the reform requirements by conducting a comparative study analysis with a framework proposal to amend the Iraqi Audit directory number statement (6) issued by the Accounting and Auditing Standards Board of the Republic of Iraq dated 08/24/2002 on audit planning and supervision on the basis of the latest versions of international auditing standards in this regard.The researchers concluded that there is a need to update the standards (evidence) audit accredited in the Republic of Iraq in accordance with international auditing standards to meet the requirements of the report of the external auditor requirements of the financial community, which is reflected in the final outcome of the fight against corruption and hazardous forms and achieve the anticipated reform requirements.In light of the findings the researchers several recommendations, including offering to emphasize the importance of conferences, seminars and workshops held as well as training programs to promote the importance of keeping up internationally recognized auditing standards to elevate effectively audit process and its role in the fight against corruption and the establishment of administrative reform expected.